CCL22 and Leptin associated with steroid resistance in childhood idiopathic nephrotic syndrome - Zhaoyang, Peng; Wei, Li; Yanyan, Jin; Wenqing, Xiang; Haidong, Fu; Jianhua, Mao (Frontiers in Pediatrics, 2023)
Objective Previous studies have indicated a decrease in T regulatory cells (Tregs) among patients with steroid-resistant nephrotic syndrome. CCL22 and Leptin influenced the immune function of Tregs through their respective pathways. This study aimed to compare patients with steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) in terms of CCL22 and Leptin levels. Methods This prospective study included 117 children diagnosed with idiopathic nephrotic syndrome (INS). Peripheral blood samples were collected before initiating steroid therapy, and serum levels of CCL22 and Leptin were measured. Patients were categorized into three groups based on their response to steroid treatment. Renal biopsies were recommended for all children diagnosed with INS, with higher acceptance rates in glucocorticoid resistance patients. Results Based on the response to steroid treatment, 117 children were divided as groups of SSNS (82 cases), frequent relapse nephrotic syndrome (FRNS) (10 cases), and SRNS (25 cases). A total of 41 patients underwent kidney biopsy, 11 cases (13.4%) in SSNS, 7 cases (70.0%) in FRNS and 24 cases (96.0%) in SRNS. 30 cases were minimal change disease (MCD), 9 cases were mesangial proliferative glomerulonephritis (MsPGN) and 3 cases were focal segmental glomerulosclerosis (FSGS). The levels of Leptin were significantly higher in SR patients (1208.1 ± 1044.1 pg/ml) compared to SS patients (515.4 ± 676.9 pg/ml) and controls (507.9 ± 479.8 pg/ml), regardless of the pathological type. CCL22 levels were significantly elevated in SRNS (92.2 ± 157.0 pg/ml), but the difference seemed to be attributed to the specific type of pathology, such as Minimal change disease (MCD) (127.4 ± 206.7 pg/ml) and focal segmental glomerulosclerosis (FSGS) (114.8 ± 22.0 pg/ml). For SRNS prediction, the AUC of Leptin, CCL22, and the joint prediction index were 0.764, 0.640, and 0.806, respectively. Conclusion Serum levels of CCL22 and Leptin, detected prior to steroid therapy, were associated with steroid resistance in childhood INS.